Correlation between clinical and histopathological findings of five puzzling cases of cutaneous tuberculosis - Miranda, Eliza; Widaty, Sandra; Sirait, Sondang Pandjaitan; Rizky, Luddwi Achmad; Menaldi, Sri Linuwih; Lim, Henry W (UI Scholars Hub, 2020)
Background: Cutaneous tuberculosis refers to the clinical manifestation of extrapulmonary tuberculosis affecting the skin. Determining the type of cutaneous tuberculosis from a patient afflicted with is challenging because clinical and histopathological similarities exist between types. Moreover, confirming a diagnosis of cutaneous tuberculosis is difficult because of its similarity with other diseases. For instance, typical and atypical cutaneous tuberculosis may have similar manifestations, but each disease is managed by completely different approaches. Microbiological examination with polymerase chain reaction and bacterial culture are the gold standard methods used to confirm a diagnosis of cutaneous tuberculosis. However, results often demonstrate negative findings. Case Illustration: Five cases of cutaneous tuberculosis, which include two cases of tuberculosis verrucosa cutis, two cases of scrofuloderma, and one case of lupus vulgaris were presented in this article. Four of the five cases demonstrated significant improvement after initiation of an antituberculosis drug regimen. Discussion: Diagnosis of cutaneous tuberculosis in these cases was confirmed through clinical findings and histopathological and microbiological examination. Conclusion: A negative result following microbiological examination does not completely exclude the diagnosis of cutaneous tuberculosis. Investigating the pathognomonic findings of cutaneous tuberculosis through histopathological examination is important to differentiate among its types correctly. Therefore, correlations between clinical and histopathological results are essential to establish a diagnosis of cutaneous tuberculosis.